MCRMiner: a Tool to Support Empirical Studies on Modern Code Review - Ferreira, Igor; Nunes, Ingrid (Anais da Escola Regional de Engenharia de Software (ERES), 2019)
Modern Code Review (MCR) has been increasingly adopted in the industry and open source development. It is a lightweight code review process, being asynchronous and tool-supported. Due to the use of tools and their underlying databases, much data associated with MCR has become available, leading to many research studies to understand and improve this process. The first step in these studies typically requires learning and accessing the API of an MCR repository, and exporting it to a particular format to be analyzed. In this paper, we introduce a tool, named MCRMiner, which automates this step to ease the conduction of empirical studies in the context of MCR. The framework provides a graphical interface and the infrastructure needed to access an MCR repository, import its data, and export them to formats typically used to process this kind of data. MCRMiner allows accessing repositories from Gerrit, an MCR tool, but is implemented as a framework so that it can be instantiated to work with other MCR tools.